The Literature Study: Pap Smear as a Method for Early Detection of Cervical Cancer: Studi Literatur : Pap Smear sebagai Metode Deteksi Dini Kanker Serviks - Khusnul Mulya Kautsar (Bandung Conference Series: Medical Science, 2023)
Cervical cancer has the third highest mortality rate in the world from all cancer cases. This figure can be prevented through pap smear examination. This study aims to collect adequate data regarding the pap smear as a method of early detection of cervical cancer. The method used is a literature study by collecting several previous studies on pap smears as a method of early detection of cervical cancer. The results of this study explain the pap smear starting from history, definition, principles, purposes, benefits, recommendations, examination procedures, and interpretation of the results. Thus, it can be concluded that the pap smear is an examination that aims to see pre-cancerous lesions which is recommended for women aged 30-60 years every three years to prevent cervical cancer.